Luminescent properties of active optical fibers - Żmojda, Jacek; Miluski, Piotr; Kochanowicz, Marcin; Dorosz, Jan; Baranowska, Agata; Leśniak, Magdalena; Dorosz, Dominik (Photonics Letters of Poland, 2019)
Luminescent optical fibres are one of the most important photonics elements as they allow to construct high power fibre lasers and different unique optical sources in the broad range from UV to IR. The most important requirements cover efficient luminescence core materials and easily pumped optical fibre constructions. Depends on the applications the variety of optical fibres have been proposed based on glasses and polymers. In the paper some recent constructions developed in Bialystok Photonics Group have been shown. Full Text: PDF References A. Zajac, D. Dorosz, M. Kochanowicz, M. Skórczakowski, J. Świderski, "Fibre lasers - conditioning constructional and technological", Bull. Pol. Ac.: Tech. 58, 4 (2010) CrossRef M. Kochanowicz, J. Zmojda, P. Miluski, A. Baranowska, M. Leich, A. Schwuchow, M. Jager, M. Kuwik, J. Pisarska, W. A. Pisarski, D.Dorosz, "Tm3+/Ho3+ co-doped germanate glass and double-clad optical fiber for broadband emission and lasing above 2 µm", Optical Materials Express, 9, 3 (2019) CrossRef J. Zmojda, M. Kochanowicz, P. Miluski, W.A., Pisarski, J. Pisarska, R. Jadach, M. Sitarz, D. Dorosz, "Structural and optical properties of antimony-germanate-borate glass and glass fiber co-doped Eu3+ and Ag nanoparticles", Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 201 (2018) CrossRef P. Miluski, M. Kochanowicz, J. Zmojda, A. Baranowska, D. Dorosz, "Energy transfer of Tb(tmhd)3 - Rhodamine B in poly(methyl methacrylate) fiber for new photonic applications", Optical Materials 87, 132 (2019) CrossRef